Faktor-Faktor Keputusan Melakukan Pinjaman Online: Inklusi Keuangan Sebagai Pemoderasi - Tio Waskito Erdi (Journal of Trends Economics and Accounting Research, 2023)
This study aims to analyze financial literacy, lifestyle, and the consumptive nature of online loans with financial inclusion as a moderation. In research conducted, a person's decision to take a loan online can be measured using the Partial Least Square (PLS)-based Structural Equation Modeling (SEM) method. This research design is quantitative, with the population in this study being individuals who make loan decisions online. The sample selection technique used purposive sampling with data collection methods in the form of a questionnaire (questionnaire) with a total of 100 respondents. The results showed that financial literacy and lifestyle variables had a positive effect on online loans, consumptive nature had a negative effect on online loans, while financial inclusion could moderate financial literacy, lifestyle, consumptive nature of online loans